2007
DOI: 10.1111/j.1399-0039.2007.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Seventeen novel alleles add to the already extensive KIR3DL3 diversity

Abstract: Exons 2-9 of KIR3DL3 alleles were characterized by genomic DNA sequencing in two families and in 78 bone marrow transplant samples. Several strategies were used to isolate single alleles for characterization and to resolve alternative allele combinations. We describe 17 novel 3DL3 alleles carried by 30 individuals. Compared with the most closely matched alleles, the new alleles differ by from one to three nucleotides and from zero to three amino acids. The majority of the substitutions were shared with other 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…KIR3DL3, another unexpressed gene, is also highly polymorphic. 30,31 KIR3DL3 and KIR2DL5B share several common features including their location in the centromeric half of the KIR gene complex, conservation in hominoids and they are Link between KIR2DL5 alleles and activating KIRs Z Du et al predicted to encode inhibitory receptors of unknown ligand specificity. 4,10 However, it is not clear what drives the sequence polymorphism of these unexpressed loci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KIR3DL3, another unexpressed gene, is also highly polymorphic. 30,31 KIR3DL3 and KIR2DL5B share several common features including their location in the centromeric half of the KIR gene complex, conservation in hominoids and they are Link between KIR2DL5 alleles and activating KIRs Z Du et al predicted to encode inhibitory receptors of unknown ligand specificity. 4,10 However, it is not clear what drives the sequence polymorphism of these unexpressed loci.…”
Section: Discussionmentioning
confidence: 99%
“…A KIR2DL5-specific forward primer 2DL5PF1 recognizing the promoter region (at B670 bp upstream of the translation-start codon) and a reverse primer 2DL5C2R1 recognizing the 3 0 UTR (at B262 bp downstream of the translation-stop codon) were used to amplify both KIR2DL5A and B genes. The PCR amplifications were performed in a reaction volume of 30 Two ml of PCR amplified products were electrophoresed on a 1% agarose gel supplemented with 0.1 mg/ml ethidium bromide, and examined for the single band of B10 kb size.…”
Section: Samplesmentioning
confidence: 99%
“…The strong linkage disequilibrium between KIR2DS2 and KIR2DL2 12 extends into the 3Ј exons of the highly polymorphic framework gene, KIR3DL3 for which ligands and functions are unknown. 37,38 Consequently, genetic analysis alone is unlikely to distinguish the contribution of individual Cen-B genes. Functional studies will be required to define the mechanism by which NK cells reconstituting from the transplanted hematopoietic stem cells of Cen-B/B donors protect against relapse in AML.…”
Section: Discussionmentioning
confidence: 99%
“…While data on KIR2DL4 and KIR3DL2 alleles in African populations is limited, many of the KIR3DL3 alleles observed in this cohort of African Americans, KIR3DL3*00208 , *01406 , *01502 , *02502 , *032 , *034, and *035, were originally described in a West African population from Ghana (IPD-KIR database version 2.3.0; submitted by Dr. Parham) and thus far have not been observed in populations of European origin (Hou et al 2007). Studies of genome-wide polymorphisms have demonstrated that the African ancestry contribution to African Americans is approximately 80% (Tishkoff et al 2009).…”
Section: Discussionmentioning
confidence: 86%
“…Only three individuals were apparent homozygotes; all three carried alleles present at frequencies >5%. Two of the common alleles found in African Americans were observed at frequencies over 5% in European Americans— KIR3DL3*003 (22%) and *00901 (12%)(Hou et al 2007). The third common allele in European Americans, KIR3DL3*00101 (14%), was found at a frequency of 2.5% in African Americans and could derive from admixture.…”
Section: Resultsmentioning
confidence: 99%